Devoted or negotiated routes of adherence: Narratives of patients with obstructive sleep apnoea using a continuous positive airway pressure device - Margareta Møkleby; Anne Marit Mengshoel (Wiley, 2019)
Abstract Aims To explore the narratives of patients about receiving a diagnosis of obstructive sleep apnoea and using a continuous positive airway pressure device. Design A qualitative design with a narrative approach. Methods Participants with personal experience of using a continuous positive airway pressure device were recruited through purposive sampling. Two women and five men were interviewed in 2017. The data material was subjected to a narrative analysis. Results Two storylines portraying two different trajectories of continuous positive airway pressure use were identified: "A route of devotion" reflects patients experiencing immediate health benefits, which lead to committed use. "A route of negotiations" is characterized by more irregular use, and the perceived benefits were less evident than for those displaying a devoted route. Individuals adjust to a continuous positive airway pressure device differently based on their prior and present life situation and whether use of the device is experienced as an opportunity to regain ordinary life or as an obstacle to maintaining ordinary life.